2009
DOI: 10.2478/v10078-009-0028-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Levels of the Young Adults in an Economically Developing Country: The Turkish Sample

Abstract: The purpose of this study was to examine the physical activity levels of the young adults in Turkey, selected as an example of an economically developing country.A total of 1027 university students voluntarily participated in this study. The sport and household activity indexes of the Physical Activity Assessment Questionnaire (PAAQ) were administered to the subjects. Student t-test showed gender differences in the intensity of the sport activities index (p<0.001). The results of 2 (gender) x 2 (intensity of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
(41 reference statements)
5
13
0
Order By: Relevance
“…Except the evidence reported in Turkish National Burden of Disease report, I only reached two studies (Aktener et al, 2006;Haşıl-Korkmaz & Arabacı, 2008 Considering the above mentioned studies (Turkish National Burden of Disease, 2004;Aktener, 2006;Haşıl-Korkmaz & Arabacı, 2008;Kin-İsler et al, 2009;Karaca et al, 2009;Cengiz et al, 2009), it can be stated that woman population in Turkey have a high risk of physical inactivity related health problems.…”
Section: Women and Physical Activitymentioning
confidence: 89%
See 2 more Smart Citations
“…Except the evidence reported in Turkish National Burden of Disease report, I only reached two studies (Aktener et al, 2006;Haşıl-Korkmaz & Arabacı, 2008 Considering the above mentioned studies (Turkish National Burden of Disease, 2004;Aktener, 2006;Haşıl-Korkmaz & Arabacı, 2008;Kin-İsler et al, 2009;Karaca et al, 2009;Cengiz et al, 2009), it can be stated that woman population in Turkey have a high risk of physical inactivity related health problems.…”
Section: Women and Physical Activitymentioning
confidence: 89%
“…In addition, most of the above mentioned previous studies in Turkish context conducted in school aged population (Daskapan et al, 2006;Savci et al, 2006;Cengiz et al, 2009;İnce & Ebem, 2009;Koca et al, 2009;Kin-İşler et al, 2009;Karaca et al , 2009). This causes a serious limitation in the generalization of the findings to older adult population.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Kudaş et al (2005) reported that boys were more active in both school and leisure time, this difference become more higher in the schooltime and the physical activity levels of female students are lower both in school and their leisure time in their study having 198 participants (n= 106 females, n=92 males) in 5th and 6th grade students aiming at determining their physical activity levels and eating habits. Jimmy et al (2007) has reached the conclusion that males prefer to participate in more intense activities in the study 209 students partipated in who were between 4-9 years, in 9-12 grades in the city of Nendaz, Switzerland, investigating the physical activity levels of them Karaca et al (2009) have reached the conclusion that men spend more time in intense activities while walking activities are more likely preferred by women in the study in which 1027 university students participated to investigate physical activity levels iof them;. Akandere et al (2008) found that women were less active at work than men in the study in which the physical activity levels of Kick Boxing coaches were evaluated.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Akandere et al (2008) found that women were less active at work than men in the study in which the physical activity levels of Kick Boxing coaches were evaluated. Karaca et al (2009) stated that most of the women spent their time by housework or sitting in their homes. This is thought to be due to the fact that women spend more time at home.…”
Section: Discussion and Resultsmentioning
confidence: 99%